Montenegro : Technical Assistance Report-Financial Soundness Indicators Mission (November 29. (IMF Staff Country Reports; Country Report, 2019)
This Technical Assistance (TA) report focuses the compilation of financial soundness indicators (FSI) for the deposit takers (DTs), which cover 15 commercial banks, using the chart of accounts (COAs) and supervisory series as source data. The regulatory and accounting practices of the DTs are broadly in line with the FSI Guide, which defers to Basel principles and International Accounting Standards. The mission recommended an action plan with the following priority recommendations to support progress in the FSI compilation. The mission highlighted the need to complement the FSI data with the corresponding metadata. Metadata should also contain information on the content and coverage of the FSIs, as well as the accounting conventions and other national guidelines. As the financial performance of commercial banks' counterpart sectors as well as key markets has direct impact on the soundness of the financial sector, it is recommended to coordinate with regulators of other financial institutions that are not under the Central Bank of Montenegro's supervision to draw a work program to collect data for compiling FSIs for other financial corporations.